Impact of traditional Chinese Baduanjin exercise on menstrual health among international female students studying in China: a randomized controlled trial - Alkhatib, Asem; Alshikh Ahmad, Hoda; Zhang, Ci; Peng, Wenwen; Li, Xianhong (Frontiers in Public Health, 2024)
Background: Menstrual symptoms were the common complaints of international female students during the acculturation period, and it negatively affected those women's daily life and school performance. The present study aimed to evaluate the effectiveness of the traditional Chinese Baduanjin exercise on reducing the menstrual symptoms for international female students studying in China during the acculturation period.We conducted a randomized controlled trial among 62 international female students who suffered the menstrual symptoms during the first 6 months after arriving in China. The study was carried out at three campuses of the two largest universities in a capital of a province in south central China from March to October 2021. After screening, participants were randomly assigned to control or intervention group. The intervention group engaged in 24 weeks of Baduanjin exercise for at least 30 minutes per day. The menstrual symptoms, sociocultural adaptation, perceived stress, and sleep quality were evaluated at baseline, the 12 th week and the 24 th week. Chi-square test or Fisher's exact test, paired sample t-test, and Multivariate analysis of variance (MANOVA) were adopted to analyze the data using SPSS 25.0 software.The 62 enrolled participants came from 30 countries. The mean age of them was 27.87 ± 5.58 years old. None of the participants reported adverse event. Results of the MANOVA test showed the traditional Chinese Baduanjin exercise reduced the total score of MSQ among international female students (intervention: 47.83 ± 8.71 vs. control: 65.12 ± 16.86; F=19.49, P<0.01). In addition, results of the MANOVA indicated the statistically significant decreases in scores for the two subscales of MSQ: premenstrual symptoms (intervention: 17.07 ± 3.33 vs. control: 28.42 ± 7.56; F=44.70, P<0.01) and menstrual pain (16.03 ± 4.53 vs. 19.58 ± 5.14; F=6.50, P<0.05). Moreover, results showed traditional Chinese Baduanjin exercise reduced the scores of sociocultural adaptation level, perceived stress level, and sleep quality, and improved the blood progesterone hormone and blood estrogen hormone.Conclusions: Regular Baduanjin exercise is a safe, acceptable, and effective exercise to promote international female students' menstrual health, reduce stress level and improve sleep quality.